Peroxisome Proliferator-Activated Receptors: Experimental Targeting for the Treatment of Inflammatory Bowel Diseases - Decara, Juan; Rivera, Patricia; López-Gambero, Antonio Jesús; Serrano, Antonia; Pavón, Francisco Javier; Baixeras, Elena; Rodríguez de Fonseca, Fernando; Suárez, Juan (Frontiers in Pharmacology, 2020)
The peroxisome proliferator-activated receptors (PPARs) are a group of nuclear receptor proteins that promote ligand-dependent transcription of target genes that regulate energy production, lipid metabolism, and inflammation. The PPAR superfamily comprises three subtypes, PPARα, PPARγ, and PPARβ/δ, with differential tissue distributions. In addition to their different roles in the regulation of energy balance and carbohydrate and lipid metabolism, an emerging function of PPARs includes normal homeostasis of intestinal tissue. PPARα activation represses NF-κB signaling, which decreases the inflammatory cytokine production by different cell types, while PPARγ ligands can inhibit activation of macrophages and the production of inflammatory cytokines, such as TNF-α, IL-6 and Il-1β. In this regard, the anti-inflammatory responses induced by PPAR activation might restore physiopathological imbalances associated with Inflammatory Bowel Diseases (IBD). Thus, PPARs and their ligands have important therapeutic potential. This review briefly discusses the roles of PPARs in the physiopathology and therapies of the most important IBDs, Ulcerative Colitis (UC) and Crohn’s Disease (CD), as well some new experimental compounds with PPAR activity as promising drugs for IBD treatment.